Evaluation of Pathogenicity to Spodoptera litura Fabricius of Different Beauveria bassiana Vuillemin Isolates Mass Multiplied on Economically Viable Substrates - Rajanikanth, P.; Subbaratnam, G. V.; Rahaman, S. J. (International Journal of Bio-resource and Stress Management, 2011)
Six isolates of Beauveria bassiana were mass multiplied using five economically viable substrates, viz. sorghum, rice bran, rice husk, press-mud and bagasse to identify the suitable substrate as wells as the vigorous isolate(s) for large scale multiplication. The results of the study showed sorghum as the most suitable substrate for large scale mass multiplication as the conidia harvested from sorghum recorded highest mortality of Spodoptera litura. Among six isolates, the isolate Bb-5A was found most virulent as it recorded highest mortality of Spodoptera litura mass multiplied on all the substrates.